The princess of the Fillmore Street School - Sharmat, Marjorie Weinman; Sharmat, Mitchell (New York, N.Y. : Delacorte Press, 1989)
Perfect Desiree seeks the help of wealthy problem solver, Olivia Sharp, in becoming princess of the school.
Keywords: Schools